LEADERSHIP AND MANAGEMENT IN HEALTHCARE FACILITIES 2022 - Mashari Shadid Dayf Allah Almutayri; Abdulhakim Salman Alsulayih; Faisal Shudayyid Dhaifallah Almutairi; Talal Ayedh Ghazi Almutairi (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Leadership and management in healthcare facilities play a critical role in ensuring the delivery of quality patient care, efficient operations, and effective decision-making. This essay explores the importance of leadership and management in healthcare facilities at the Master level. The essay examines the key roles and responsibilities of healthcare leaders and managers, the challenges they face, and the strategies they employ to overcome these challenges. Additionally, the essay highlights the significance of effective leadership and management in promoting a culture of continuous improvement and innovation in healthcare settings.